Uma análise do grau comparativo nos materiais didáticos de língua inglesa via teoria das operações predicativas e enunciativas - Ferreira, Marília Dias [UNESP] (2015)
This is a work focused on the study of comparative degree as a linguistical marker and the senses that this construction can generate. Our research is directly related to the project Articulation of lexicon and grammar and organization of notional domains: new developments, framed in research line Teaching and Language Learning under the guidance of Professor Dr. Lecticia Marcondes Rezende of Post Graduate Program in Linguistics and Portuguese Language in UNESP - Araraquara Campus. Thus, the work makes a way to perform semantic analyses of comparative sentences found in English language teaching materials, both textbooks and grammars used in High School. Among these materials we select four grammars and four textbooks, choosing nineteen sentences to delimit the corpus for analyses in order to answer questions around the senses brought up by these sentences, sorting them, at the beginning of this research, into linear and complex sentences. Linear ones are those which have a property that determines both the comparing term and the compared one to some degree (equal, less or more); meanwhile the complex ones are those in which the property put into game features a zero or null degree in specification of compared term in relation to the one we are comparing. In order to explain the movement of language made by these sentences to account for their meanings we invest especially in the Theory of Predicative and Enunciative Operations by Antoine Culioli. Before that it was also necessary to search for foundations in logical-philosophical, grammatical and semantic grounds. Furthermore, this paper presents a contrastive reading of the trajectory of National Curriculum Parameters for High School and Contents of Common Ground for Elementary and High School in Minas Gerais around the study of foreign languages in regular school, founded in Culioli theory. Through the notions that involve extra-linguistic reality and the subjects enunciator and/or ...